Does a history of physical exposures at work affect hand-grip strength in midlife? A retrospective cohort study in Denmark - Anne Møller; Susanne Reventlow; Åse Marie Hansen; Lars L Andersen; Volkert Siersma; Rikke Lund; Kirsten Avlund; Johan H Andersen; Ole Steen Mortensen (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVE: The aim of this cohort study was to examine associations between physical exposures throughout working life and hand-grip strength (HGS) in midlife. METHODS: The Copenhagen Aging and Midlife Biobank (CAMB) provided data about employment and HGS for 3843 Danes. Individual job histories, including duration of employment in specific jobs, were assigned exposures from a job exposure matrix. Exposures were standardized to ton-years (lifting 1000 kg each day in one year), stand-years (standing/walking for six hours each day in one year) and kneel-years (kneeling for one hour each day in one year). The effects of exposure-years on HGS were analyzed as linear effects and cubic splines in multivariate regression models, adjusted for potential confounders. RESULTS: Mean age was 59 years among both genders and HGS was 49.19 kg [standard deviation (SD) 8.42] and 30.61 kg (SD 5.49) among men and women, respectively. Among men, exposure to kneel-years was associated with higher HGS [>0.030 kg (P=0.007) per exposure-year]. Ton- and stand-years were not associated with HGS among either men or women in linear analyses. In spline regression analyses, associations between ton- and stand-years and HGS were non-linear and primarily positive among men. Among women, the associations were non-linear and, according to ton-years, primarily negatively associated with HGS but statistically insignificant. CONCLUSION: A history of physical exposures at work explained only a minor part of the variation in HGS, though exposure to kneeling throughout working life was associated with a slightly higher HGS among men. Exposure to lifting and standing/walking was not associated with HGS.